2005
DOI: 10.1111/j.1523-1739.2005.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

A Landscape Approach to Biodiversity Conservation of Sacred Groves in the Western Ghats of India

Abstract: Although sacred groves are important for conservation in India, the landscape that surrounds them has a vital influence on biodiversity within them. Research has focused on tree diversity inside these forest patches. In a coffee-growing region of the Western Ghats, however, landscape outside sacred groves is also tree covered because planters have retained native trees to provide shade for coffee plants. We examined the diversity of trees, birds, and macrofungi at 58 sites-10 forest-reserve sites, 25 sacred gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(120 citation statements)
references
References 47 publications
(40 reference statements)
3
114
0
3
Order By: Relevance
“…As a result of these restrictions, the biodiversity in such sacred groves are preserved over many generations, and still exist today. The sacred groves are the last home of some endangered species, as observed in Kodagu district of southern Indian state of Karnataka [24], and also are known to represent the only exiting climax vegetation communities in northeastern India [23]. Numbers of studies have supported the role of sacred grove in conservation of biodiversity across the different parts of India including West Bengal [25], Northeast India [26] and Eastern Ghats [12].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these restrictions, the biodiversity in such sacred groves are preserved over many generations, and still exist today. The sacred groves are the last home of some endangered species, as observed in Kodagu district of southern Indian state of Karnataka [24], and also are known to represent the only exiting climax vegetation communities in northeastern India [23]. Numbers of studies have supported the role of sacred grove in conservation of biodiversity across the different parts of India including West Bengal [25], Northeast India [26] and Eastern Ghats [12].…”
Section: Discussionmentioning
confidence: 99%
“…Sacred sites have been under the protection of local people for their spiritual value for generations and might be the oldest forms of protected areas in human history (Dudley et al 2009). It has been shown that the traditional practice of sacred site worship may make significant contributions to protecting endangered species and conserving biodiversity (Decher 1997, Mgumia and Oba 2003, Bhagwat et al 2005a, 2005b, Bossart et al 2006, and few studies have documented the social mechanisms behind those traditional practices (Malhotra 2001, Tengö et al 2007. Recognizing the value of sacred sites in contemporary conservation systems is advocated by numerous scholars and international nongovernmental organizations (NGOs) and has received increasing attention over the last two decades (Daniels et al 1993, Xu et al 2005, Bhagwat and Rutte 2006, Dudley et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Kerala is one of the state having maximum number of Sacred Groves. They are traditionally conserved as a part of natural worship and these practices have played an important role in protection of biodiversity (Bhagawat et al, 2005;Bhagawat & Rutte, 2006.). The sacred grove performs several ecological functions, which directly or indirectly helps to maintain ecosystem health of all other interacting landscape units.…”
Section: Introductionmentioning
confidence: 99%